The neurobiological basis of sleep: Insights from Drosophila - Ly, Sarah; Pack, Allan I.; Naidoo, Nirinjini (Neuroscience and biobehavioral reviews, 2018)
•Drosophila sleep is regulated by multiple neurotransmitters and intracellular signaling pathways in the brain.•Many of the identified regulators of Drosophila sleep exhibit conserved role in mammalian systems.•Evidence in Drosophila and across multiple species indicates that sleep functions to regulates a wide range of physiological processes.•Technical considerations of fly studies include: limitations in single-fly sleep analysis, sex differences, and brain development effects. Sleep is a biological enigma that has raised numerous questions about the inner workings of the brain. The fundamental question of why our nervous systems have evolved to require sleep remains a topic of ongoing scientific deliberation. This question is largely being addressed by research using animal models of sleep. Drosophila melanogaster, also known as the common fruit fly, exhibits a sleep state that shares common features with many other species. Drosophila sleep studies have unearthed an immense wealth of knowledge about the neuroscience of sleep. Given the breadth of findings published on Drosophila sleep, it is important to consider how all of this information might come together to generate a more holistic understanding of sleep. This review provides a comprehensive summary of the neurobiology of Drosophila sleep and explores the broader insights and implications of how sleep is regulated across species and why it is necessary for the brain.